Dynamic partitioning of mitotic kinesin-5 cross-linkers between microtubule-bound and freely diffusing states - Cheerambathur, Dhanya K. (The Rockefeller University Press, 2008)
The dynamic behavior of homotetrameric kinesin-5 during mitosis is poorly understood. Kinesin-5 may function only by binding, cross-linking, and sliding adjacent spindle microtubules (MTs), or, alternatively, it may bind to a stable “spindle matrix” to generate mitotic movements. We created transgenic Drosophila melanogaster expressing fluorescent kinesin-5, KLP61F-GFP, in a klp61f mutant background, where it rescues mitosis and viability. KLP61F-GFP localizes to interpolar MT bundles, half spindles, and asters, and is enriched around spindle poles. In fluorescence recovery after photobleaching experiments, KLP61F-GFP displays dynamic mobility similar to tubulin, which is inconsistent with a substantial static pool of kinesin-5. The data conform to a reaction–diffusion model in which most KLP61F is bound to spindle MTs, with the remainder diffusing freely. KLP61F appears to transiently bind MTs, moving short distances along them before detaching. Thus, kinesin-5 motors can function by cross-linking and sliding adjacent spindle MTs without the need for a static spindle matrix.